Characterization Of Moringa (Moringa Oleifera Lam.) Leaf Water Extracts By Chemical And Microbiology - Siti Rahayu Rachmawati; junie Suriawati (Politeknik Kesehatan Kemenkes Jakarta II, 2019)
Moringa leaves or referred to Moringa oleifera Lam. are belong to the Moringaceae tribe. This plant is reported to have antibacterial activity and high nutritional value. To be used as an active ingredient in food preparations, it needs to be made in the form of extracts. The study aims to determine the characteristics of Moringa leaf water extract. In this study, Moringa leaves were extracted with a water solvent. Chemical characterization of Moringa leaf extract includes qualitative phytochemical tests and nutritional values ​​(water content, ash, protein, fat, and carbohydrate). Whereas in microbiology, they include microbial contamination (Total Plate Count and Total Yeast and Mold Count). The results of characterization testing of the extracts showed that the water extract of Moringa leaves contain active compounds: flavonoids, phenols, triterpenoids/steroids, saponins, and tannins. Microbial contamination contained in the water extract of Moringa leaves are Total Plate Count value of 0 colonies/g and Mold/Yeast count value of 0 colonies/g and contain nutritional values such as water (75.85%), ash (3.87%), protein (6.27%), fat (<2.20 %) and carbohydrate (14.01%).